Kinds of blue: diversity in UN peacekeeping missions and civilian protection - Bove, V; Ruggeri, A (Cambridge University Press, 2015)
For a given number of troops in a peace operation, is it advisable to have soldiers from a single country, or should the UN recruit peacekeepers from a variety of donor countries? Since 1990, the number of contributors to peace operations has grown threefold, and most operations have carried the mandate to protect civilians. This article explores the effect of diversity in the composition of a mission, measured by fractionalization and polarization indices, on its performance in protecting civilians in Africa in the period 1991–2008. It finds that mission diversity decreases the level of violence against civilians, a result that holds when geographic and linguistic distances between countries are considered.